ANALYZING ATTITUDES TOWARDS SCIENCE AND RELIGION BETWEEN NATIONAL AND ISLAMIC SCHOOLS IN INDONESIA: A CASE STUDY - Saputra, Winata Tegar; Winarno, Nanang; Rusyati, Lilit; Firdaus, Rohim Aminullah; Mustikasari, Vita Ria (Universitas Pakuan, 2024)
Given that Muslims make up the majority in Indonesia, students' perspectives on science are influenced by their religious beliefs. This research aims to analyze the differences in attitudes toward science and religion between national and Islamic schools. This study employed a survey method to look at the views of students in national and Islamic schools. Two groups comprise the 420 Indonesian secondary school students that comprise the research sample: 212 students from national schools and 208 from the renowned